Optimum Performance-Based Seismic Design Using a Hybrid Optimization Algorithm - Talatahari, S.; Hosseini, A.; Mirghaderi, S. R.; Rezazadeh, F. (Mathematical problems in engineering, 2014)
A hybrid optimization method is presented to optimum seismic design of steel frames considering four performance levels. These performance levels are considered to determine the optimum design of structures to reduce the structural cost. A pushover analysis of steel building frameworks subject to equivalent-static earthquake loading is utilized. The algorithm is based on the concepts of the charged system search in which each agent is affected by local and global best positions stored in the charged memory considering the governing laws of electrical physics. Comparison of the results of the hybrid algorithm with those of other metaheuristic algorithms shows the efficiency of the hybrid algorithm.